Penerapan Teknologi Penggunaan Probiotik Raja Siam Untuk Meningkatkan Pertumbuhan Larva Ikan Baung Pada Kelompok Perikanan Sawah Mandiri, Desa Sawah, Kecamatan Kampar Utara, Kabupaten Kampar, Riau - Sukendi, Sukendi; Putra, Ridwan Manda; Eddiwan, Eddiwan; Nurhidayah, Tengku; Thamrin, Thamrin; zulkarnaini, Zulkarnaini (Unri Conference Series: Community Engagement, 2025)
The objective of this community service activity is to provide knowledge and technology on the use of Probiotik Raja Siam in improving the growth and survival rate of Asia redtai catfish larvae in the Sawah Mandiri Fisheries Group, Sawah Village, Kampar Utara Subdistrict, Kampar Regency, Riau. The implementation methods included lectures, discussions, and hands-on field practice. Lectures and discussions were conducted in the group meeting room, covering the benefits of soaking asia redtai catfish larvae using Probiotik Raja Siam. Field practice was carried out at the hatchery, where participants were guided through the soaking process, distribution, and initial care of the larvae. The knowledge evaluation results showed a significant improvement in understanding. Out of the 13 group members present, 10 (76.92%) were able to absorb the material with an excellent rating, 2 (15.38%) with a good rating, and 1 (7.69%) with a satisfactory rating. The skill evaluation results showed that group members were able to apply the use of Raja Siam Probiotics to support the growth of asia redtai catfish larvae. Meanwhile, the impact evaluation results indicated that members of the Independent Rice Field Fisheries Group had begun using Raja Siam Probiotics to accelerate the growth of Asia redtai catfish larvae.